A 15 amino acid fragment of influenza nucleoprotein synthesized in the cytoplasm is presented to class I-restricted cytotoxic T lymphocytes. - Gould, K; Cossins, J; Bastin, J; Brownlee, G; Townsend, A (1989)
A recombinant vaccinia has been designed to express amino acids 366-379 of influenza nucleoprotein, previously shown to be the minimal epitope recognized by a class I-restricted cytotoxic T cell clone. Target cells infected with the recombinant vaccinia virus expressing this peptide are recognized by CTL as efficiently as target cells expressing the complete nucleoprotein. The results imply the existence of a peptide transport system that constitutively passes the products of degraded proteins from the cytoplasm into a membrane-bound compartment of the cell.